Dampak Psikologis Penggunaan Aplikasi Anā Muhtarif Al Khaṭ Terhadap Perkembangan Ilmu Kaligrafi Arab - Septiana, Eka; S, Fahrurrozi; Nasution, Aulia Ramadhani (Jurnal Psikotes, 2024)
Calligraphy is a branch of Arabic knowledge that focuses on the art of writing in Arabic. The art of writing has developed over time. Especially nowadays, an application called Anā Muhtarif Al Khaṭ has emerged, where this application has an influence in the field of calligraphy. Based on this, the author is interested in knowing the impact of using the Anā Muhtarif Al Khaṭ application on calligraphy science. In this research, the author uses qualitative methods, where the author collects data and information through literature studies and trials. The results of this research are that this application has a good influence, especially for audiences who want to create calligraphic works who do not have special talent or expertise in the field of calligraphic writing. On the other hand, this application also has negative impacts, including threatening the history of calligraphy in terms of writing manually using a brush and canvas.